KAJIAN HISTORIS TERHADAP WABAH PADA MASA NABI MUHAMMAD SAW (571-632 M) - Novita Nurlaeli Handayani (Progam Studi Sejarah Peradaban Islam (SPI), Fakultas Ushuluddin Adab dan Humaniora, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
At the time of the Prophet Muhammad SAW has experienced various kinds of challenges, one of which is a plague. The emergence of the Plague made the impact of transmission very fast and deadly. However, Prophet Muhammad SAW was able to minimize the transmission of the plague by providing a policy. This study uses the